Causal Therapy of COVID-19: Critical Review and Prospects - N. V. Beloborodova; E. V. Zuev; M. N. Zamyatin; V. G. Gusarov (Общая реаниматология)
The COVID-19 outbreak started in December 2019 in China has spread over all countries of the world within few month acquiring a pandemic nature, the incident population counting millions. The pathogenic mechanisms of the new coronaviral infection caused by never-before-seen virus SARS-CoV2 are yet to be studied. Various drugs are used for COVID-19 treatment and guidelines are continuously revised as new experience is acquired. In the current pandemic situation, it is important to provide specialists with latest information concerning efficacy and safety drugs for COVID-19 patients and promising research in this field.The purpose of the review is to critically analyze published data on outcomes of COVID-19 treatment with various drugs including potentially promising drugs.The search has been carried out through such databases as PubMed, Scopus, Cyberleninka, https://www.globalclinicaltrialsdata.com, https://clinicaltrials.gov, Cochrane Library; mostly, randomized clinical trials-2020 and papers dedicated to candidate drugs have been considered. The paper is structured based on the drug’s action mechanism and contains parts dedicated to antiviral, immunomodulatory, and antibacterial therapies. Looking for a new promising target in COVID-19 treatment, the authors focus their attention on matrix metalloproteinases (MMP), which abundance results in the destruction of extracellular matrix, epithelial and endothelial basal membranes and leads to secondary lung tissue injury. The paper provides a theoretic justification of MMP inhibitor use by an example of doxycycline and offers an efficacy study protocol for the new approach to COVID-19 therapy.Conclusion: as of now, there are no drugs which efficacy for COVID 19 has been proven. Drugs possessing multiple mechanisms of action are employed beside their specified indications, often in combinations; in this situation, additive side effects with adverse consequences for the patient can hardly be avoided. Administration of drugs with unproven efficacy may be justified only in clinical trials followed by subsequent analysis and publication of findings demonstrating that in case of success, recommendations for a majority of COVID-19 patients could be confidently issued.